Genetic and Environmental Links Between Motor Activity Level and Attention Problems in Early Childhood - Saudino, Kimberly J. (Dev Sci, 2017)
Cross-lagged biometric models were used to examine genetic and environmental links between actigraph-assessed motor activity level (AL) and parent-rated attention problems (AP) in 314 same-sex twin pairs (MZ=145, DZ=169) at ages 2 and 3 years. At both ages, genetic correlations between AL and AP were moderate (r(a2)=.35; r(a3)=.39) indicating both overlap and specificity in genetic effects across the two domains. Within- and across-age phenotypic associations between AL and AP were entirely due to overlapping genetic influences. There was a unidirectional effect of AL at age 2 predicting later AP. For AP, genetic and environmental influences from age 2 were transmitted to age 3 via stability effects and from AL. For AL, across-age effects were transmitted only via stability. These results suggest that overactivity in late infancy may impact the later development of problems related to inattention, and that genetic factors explain the association between the two domains.